Optimizing HDAC inhibitors to enhance HDR-associated CRISPR-Cas9 gene editing efficiency in vivo and in vitro - Jeong Woon Jang; Min Ji Kim; Chang Sik Cho; Jun Hee Han; Sangsu Bae; Hongjun Jeon; Dong Hyun Jo; Hye Jin Nam (Heliyon)
Gene editing by CRISPR-Cas9 via homology-directed repair (HDR) offers precise and desirable modifications, but its low efficiency remains a challenge due to the dominance of the non-homologous end joining (NHEJ) pathway in DNA repair. To identify compounds that improve HDR-associated gene editing efficiency, we established a high-throughput screening system capable of detecting HDR events and assessing cell viability simultaneously, excluding drugs with severe cytotoxicity. We screened 2485 compounds from a clinical collection library and identified several histone deacetylase inhibitors that significantly enhance HDR efficiency. Tacedinaline and entinostat exhibited the high efficiency in promoting HDR-associated gene editing among them. Notably, entinostat treatment led to a significant increase in HDR-associated gene editing in vivo. Our study provides optimized HDAC inhibitor conditions for high-efficiency HDR-associated gene editing both in vivo and in vitro.